19 + 4 12 + 19 4 12 \sqrt{19+4\sqrt{12}}+\sqrt{19-4\sqrt{12}}

Algebra Level 1

Simplify 19 + 4 12 + 19 4 12 . \sqrt{19+4\sqrt{12}}+\sqrt{19-4\sqrt{12}}.

10 9 7 8

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Datu Oen
Mar 13, 2014

Note that:

19 + 4 12 = 19 + 8 3 = 16 + 3 + 2 ( 4 3 ) 19 + 4\sqrt{12} = 19 + 8\sqrt{3} = 16 + 3 + 2(4\sqrt{3})

= 4 2 + ( 3 ) 2 + 2 ( 4 3 ) = 4 2 + 2 ( 4 3 ) + ( 3 ) 2 = 4^2 + (\sqrt{3})^2 + 2(4\sqrt{3}) = 4^2 + 2(4\sqrt{3}) + (\sqrt{3})^2

Now,

4 2 + 2 ( 4 3 ) + ( 3 ) 2 4^2 + 2(4\sqrt{3}) + (\sqrt{3})^2 is equivalent to ( 4 + 3 ) 2 (4 + \sqrt{3})^2 . That is

19 + 4 12 19 + 4\sqrt{12} = ( 4 + 3 ) 2 (4 + \sqrt{3})^2 . Taking the square root we have 4 + 3 4 + \sqrt{3}

Similarly, 19 4 12 19 - 4\sqrt{12} = ( 4 3 ) 2 (4 - \sqrt{3})^2 . Taking the square root we have 4 3 4 - \sqrt{3} .

Thus,

19 + 4 12 + 19 4 12 = ( 4 + 3 ) + ( 4 3 ) = 8 \sqrt{19 + 4\sqrt{12}} + \sqrt{19 - 4\sqrt{12}} = (4 + \sqrt{3}) + (4 - \sqrt{3}) = 8

let the given expression be equal to x.......... squaring both sides.............and then simplifying ......x=8

Ehsan Habib
Mar 19, 2014

by calculator....:D

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...